Oral hyaluronan for the treatment of knee osteoarthritis: a systematic review - Guadagna, Simone; Barattini, Dionisio Franco; Pricop, Marius; Rosu, Serban (Progress in Nutrition, 2018)
Study Objectives: Osteoarthritis (OA) is the most common chronic condition of the joints, affecting approximately 27 million of people in the US and its prevalence is predicted to grow. Recently, symptomatic slowacting drugs for osteoarthritis (SYSADOA) have been vastly studied and have generated considerable interest among clinicians and the public. In particular, the use of oral hyaluronic acid (HA) treatments for knee pain has been the source of much research and it is now widely adopted in the clinic for its safety and relative low cost. The aim of this study is to discuss the efficacy of oral HA in treating knee OA based on the most recent data from the literature as well as to encourage the use of objective measures to determine more effectively the efficacy of current therapies for knee OA. Methods: We searched the PubMed database up to 23/01/2018 based on data from randomized, double-blind, placebo-controlled trials, non-controlled trials and cohort studies conducted in adult subjects. The search words used contained the terms: oral hyaluronan (HA) and knee osteoarthritis (OA). We selected 15 relevant reports. The review was registered on PROSPERO (International prospective register of systematic reviews), registration number CRD42018104127. Results: Companies in Japan, US and Europe produced different oral supplements containing HA in various formulations, which have been tested in clinical trials. The vast majority of the studies analyzed found significant improvements of scores including VAS, WOMAC, JKOM and SF-36v2 in patients with moderate knee OA after short (1 – 4 months) daily treatments with oral HA preparations, compared to placebo-treated controls. Interestingly, few studies proposed the use of objective measures to evaluate the efficacy of HA treatments with ultrasonography and an isokinetic dynamometer, but they obtained modest and controversial results. Conclusions: Current clinical data on oral HA products for the treatment of mild to moderate knee OA are promising and in line with The European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis (ESCEO) recommendation to use SYSADOA. However, more high-quality research with larger sample sizes and longer exposures to the oral treatment is needed to confirm these data. Particularly, more effort is required to standardize the treatments (final dose of HA, molecular weight of HA and presence of other active molecules) and to assess the results on patients with objective measures.